Categorization of contemporary art collectors in Japan: clustering by art purchase motivations and psychographic characteristics - Yuki Wasano; Hiroshi Onishi (Cogent Social Sciences, 2024)
In this study, we categorized art collectors based on their motivations to purchase contemporary artworks in the Japanese art market. Applying the 14 art purchase motivations proposed by Zolfagharian and Cortes, we conducted a large-scale quantitative online survey and clustering analysis, which resulted in identifying four types of Japanese contemporary art collectors (balanced/harmonious, geek, immature, and intelligent). The characteristics of each type were examined in terms of purchasing behavior and psychographic characteristics and analyzed using a regression model, then their impact on the art market was quantified. As a result, we concluded that the intelligent type of art collector not only drives a larger amount of art consumption in the Japanese contemporary art market but also leads to the innovative image of collectors’ diversity values. It is also noted that immature collectors are important because they can be promoted to become the intelligent type. This paper is the first study to explore the purchase motivations of the Japanese contemporary art collectors based on the large-scale quantitative data which include detailed psychographic characteristics. In addition to find the four art collector types, we examine their economic and innovative value for developing practical solutions to expand the Japanese art market.